Pelatihan Microsoft Office Bagi Guru Paud Di Kota Pematangsiantar Sebagai Upaya Pengembangan Dan Peningkatan Kemampuan Dalam Menggunakan Aplikasi Olah Kata - Agus Perdana Windarto; Anjar Wanto (LPPM STIKOM Tunas Bangsa, 2020)
The results of the implementation of service activities that have been carried out that PAUD teacher's knowledge about microsoft office learning as an application of word processing is still inadequate prior to the training. This is indicated from the results of the pre-test. Activities carried out by the team of lecturers and students of STIKOM Tunas Bangsa